Performance of International Global Models and Official Tropical Cyclone Forecasts Over the Bien Dong Sea for the Period 2012–2019 - Hoa Vo Van; Hung Mai Khanh; Tien Du Duc; Lars Robert Hole; Quan Dang Dinh; Duc Tran Anh; Hang Pham Thi; Nam Hoang Gia (Advances in Meteorology)
This research validates tropical cyclone (TC) forecasts from the National Centre for Hydro-Meteorological Forecasting of Vietnam, the Regional Specialized Meteorological Center (RSMC) Tokyo, and global models (the Japanese Meteorological Agency [JMA], global spectral model [GSM], the National Centers for Environmental Prediction [NCEP], Global Forecast System [GFS], and the European Centre for Medium-Range Weather Forecasts [ECMWF] Integrated Forecasting System [IFS]) for 72 activated TCs over the Bien Dong Sea. The best quality track forecasts come from the IFS and then GFS and GSM, while the GFS provides a good intensity forecast compared to IFS and GSM. The official guidance and model track forecast tend to be slower and leftward compared to observations (negative biases of along and cross-track errors). Regarding the ECMWF’s ensemble track forecast, the strike probability forecast is quite overforecast/overconfident, especially for a lead time of 72 h and at high probabilities.